Ensemble of DNA Letters for the Design of Unique DNA Library Using a Modified Version of Multi-criteria VEDEPSO Optimizer - Selvan, K.V; Muhammad, M.S; Masra, S.M.W (IEEE, 2012)
The DNA code words designing is a multi-criteria combinatorial optimization task. The designed words should be as unique as possible, thermodynamically stable, non-self hybridized, non-cross hybridized with others and have good chemical properties. In this paper, the DNA words designing approach implied concurrent minimizations of four objective functions, H-measure, similarity, hairpin and continuity. The designations is subjected to a predefine range of melting temperature and GC-content. A novel multi-population optimizer, M-VEDEPSO, is employed to design sets of DNA strands. The algorithm runs for 10 times and as a result, each population has lower average fitness values compared to the fitness values obtained using the conventional VEDEPSO algorithm. The results obtained from the algorithm are indicated by 12 randomly selected non-dominated particles/individuals. These solutions are obtained via Pareto dominance concepts.